Identifikasi Produk Bahan Obat yang Berbahan Dasar Alga (Mikro Alga atau Makroalga) Pada Pasar Tradisional/Modern yang ada di Kota Medan - Ulfa, Syarifah Widya; Mawaddah, Hanifa; Lubis, Isnaini Rahma; Mawla, Muhammad Fazil; Amalia, Qoyum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Algae have the potential as a very useful resource for humans. Some types of algae have been known to have antioxidant, anticancer, anti-inflammatory, and antifungal properties that can help in the treatment of diseases. This research was conducted in traditional markets and modern markets in Medan City, especially on Jl. Jamin Ginting, North Sumatra. The purpose of this study was to identify the types of algae-based medicinal products (microalgae or macroalgae) available in traditional/modern markets in Medan city. The sampling method used in this study was the cruise method with purposive sampling technique. The results showed 3 types of medicines in traditional and modern markets in Medan City that are made from algae, namely Ever E 250 (Seaweed Capsules), Algae Calcium (Red Algae) and Brown Seaweed (Brown Algae). Some of the health benefits of red algae include maintaining thyroid function, lowering cholesterol and as a healthy diet menu. The benefits of brown algae include algin or alginate acid from brown algae used in ice cream formation, pill formation, ointments, tooth cleaners, and lotions. Meanwhile, green algae contain carotenoids, phycocyanin, plant sterols, and linoletat which can help maintain heart health. Keywords: Algae, medicinal ingredients, traditional market